The intellectual base and research fronts of IL-37: A bibliometric review of the literature from WoSCC - Qin, Ya-fei; Ren, Shao-hua; Shao, Bo; Qin, Hong; Wang, Hong-da; Li, Guang-ming; Zhu, Yang-lin; Sun, Cheng-lu; Li, Chuan; Zhang, Jing-yi; Wang, Hao (Frontiers in Immunology, 2022)
Background: IL-37 is a recently identified cytokine with potent immunosuppressive functions. The research fronts of IL-37 are worth investigating, and there is no bibliometric analysis in this field. The purpose of this study is to construct the intellectual base and predict research hotspots of IL-37 research both quantitatively and qualitatively according to bibliometric analysis. Methods: The articles were downloaded from the Web of Science Core Collection (WoSCC) database from the inception of the database to April 1, 2022. CiteSpace 5.8.R3 (64-bit, Drexel University, Philadelphia, PA, US) and Online Analysis Platform of Literature Metrology (https://bibliometric.com/) were used to perform bibliometric and knowledge-map analysis. Results: A total of 534 papers were included in 200 academic journals by 2,783 authors in 279 institutions from 50 countries/regions. The journal of Cytokine published the most papers on IL-37, while Nature Immunology was the most co-cited journal. The publications belonged mainly to two categories of Immunology and Cell Biology. The USA and China were the most productive countries. Meanwhile, the University of Colorado Denver in the USA produced the highest number of publications followed by Radboud University Nijmegen in the Netherlands and Monash University in Australia. Charles A. Dinarello published the most papers, while Marcel F Nold had the most co-citations. Top10 co-citations on reviews, mechanisms, and diseases were regarded as the knowledge base. The keywords co-occurrence and co-citations of references revealed that the mechanisms, immune-related disorders were the main aspects of IL-37 research. Notably, the involvement of IL-37 in various disorders and the additional immunomodulatory mechanisms were two emerging hotspots in IL-37 research. Conclusions: The research on IL-37 was thoroughly reviewed using bibliometrics and knowledge-map analysis. The present study is a benefit for academics to master the dynamic evolution of IL-37 and point out the direction for future research.